Robot Penempatan Barang Berdasarkan Kode Warna RGB Menggunakan Arduino Nano - Darusman, Darusman (INFORMATICS FOR EDUCATORS AND PROFESSIONAL : Journal of Informatics, 2024)
The RGB Color Code-Based Item Placement Robot Using Arduino Nano is a robot created to replace the role of a goods transfer vehicle. This robot has the ability to move items automatically based on RGB color codes. This research represents a type of robot that moves along a predetermined guiding line. This robot uses two DC motors that function to move the wheels, and it has sensors consisting of two pairs: an infrared sensor and a photodiode, which serve as a signal transmitter and receiver located at the bottom of the robot to detect black line paths. The RGB sensor is used for reading color codes when the robot approaches the item transfer location. The servo motor functions to move the gripper when picking up items, while the stepper motor is responsible for raising and lowering the items according to the positions that will be commanded later. Thus, overall, the system in this color-coded item transfer robot can function well